Regional employment effects of MNE offshoring - Kent Eliasson; Pär Hansson; Markus Lindvert (Örebro University School of Business, 2019)
The employment in Sweden has become more concentrated to the larger cities in Sweden (Stockholm, Göteborg and Malmö). This paper investigates whether Swedish multinational enterprises (MNEs) have contributed to that development. We examine the association between offshoring within Swedish MNEs and changes their parent employment at regional level (in local labor market regions, LA-regions). The relation may vary depending on: (i) the characteristics of the region (large city, regional center or other region) or (ii) the type of labor (skilled or less-skilled) or the type of job (routine or non-routine) in the parent. Our results reveal large spatial heterogeneities in the relationships between MNE offshoring and onshore employment in various regions. The results suggest that MNE offshoring might be a factor contributing to diverging onshore employment among Swedish regions; increased (unchanged) employment in larger cities and unchanged (decreased) employment in regional centers and other regions. Moreover, MNE offshoring seems to contribute to increased localization of skilled activities and non-routine tasks to larger cities. We use enterprise data on employment in the parents and the affiliates overseas in Swedish controlled enterprise groups with affiliates abroad (Swedish MNEs). Parent employment data are available for different regions in Sweden, skilled and less-skilled labor, as well as for various occupations.
Keywords: F14; F16; F23; J23; J24; 330; multinational enterprises (MNEs); offshoring; local labor markets; skilled and lessskilled employment; routine and non-routine and jobs